Simulation of Positive Problems in Three Dimensional ECT System - LI Yan; LI Xiang-yu; YU Dao-yang (Journal of Harbin University of Science and Technology)
Electrical capacitance tomography (ECT) has many advantages, such as noninvasion, antiinterference, and security In the past, the ECT system can only obtain twodimensional images of fluid, and the threedimensional images formed by the accumulation of twodimensional cross sections are not threedimensional images in actual sense To solve this problem, this paper from the view of theoretical analysis, used numerical analysis and functional to establish a 3D mathematical model of ECT. Meanwhile we utilized the MATLAB script to calculate the results of the mathematical model, and compared with the simulation results of ANSYS The experimental results show that the 3D ECT model can meet the requirements of Engineering applications